2022
DOI: 10.3390/nu14194138
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding in Phenylketonuria: Changing Modalities, Changing Perspectives

Abstract: Phenylketonuria (PKU) management aims to control phenylalanine (Phe) intakes. In newborns and infants this implies possible titration of Human milk (HM) with supplementation of Phe-free formula. HM benefits, better if prolonged, are well known in healthy populations, suggesting it may be used in PKU patients. Despite that, the current literature does not define recommendations on how best perform it in such a population. The main purpose of this study was to evaluate nutrition approaches in newborns and infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…All infant formulas must be safe and suitable to satisfy the nutritional requirements and promote appropriate growth and development. In infants with PKU, even if human milk or standard infant formulas can be used alongside infant Phe-free protein substitutes, to date, there are no specific indications about the proportions of the two modalities or the effects on disease control and infant growth [ 50 ]. For this reason, infant PS for PKU available on the Italian market should be the best possible alternative to exclusive maternal breastfeeding, providing the nutrient profile as well as the structural and functional effects are as similar as possible to those observed in exclusively breastfeeding or standard infant formulas.…”
Section: Discussionmentioning
confidence: 99%
“…All infant formulas must be safe and suitable to satisfy the nutritional requirements and promote appropriate growth and development. In infants with PKU, even if human milk or standard infant formulas can be used alongside infant Phe-free protein substitutes, to date, there are no specific indications about the proportions of the two modalities or the effects on disease control and infant growth [ 50 ]. For this reason, infant PS for PKU available on the Italian market should be the best possible alternative to exclusive maternal breastfeeding, providing the nutrient profile as well as the structural and functional effects are as similar as possible to those observed in exclusively breastfeeding or standard infant formulas.…”
Section: Discussionmentioning
confidence: 99%
“…It is good practice to encourage parents to keep a record of daily feeds [ 32 , 33 ]. The method of administering SF-Phe before breastfeeding has shown that infants with PKU continue to breastfeed for an older age of HM compared to the alternative methods of alternating HM and SF-Phe or expressing milk and measuring the amount administered [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acceptable blood Phe control and growth are possible with its use [6]. However, breastfeeding rates and duration of feeding in infants with PKU remain lower than in the general population [7]. There is limited research investigating the maternal experience of BF an infant with PKU.…”
Section: Introductionmentioning
confidence: 99%